Heads Up: Describing and Implementing a Time-Saving Head Strike Protocol at a Level II Trauma Center. Issue 2 (March 2018) - Wacht, Sharon; Salottolo, Kristin; Atnip, Amy; Hooks, Michelle; Bailie, Mary; Carrick, Matthew
Abstract : Head strikes can be fatal for patients taking blood thinners (anticoagulants or antiplatelets). Our trauma center instituted the "head strike protocol" to provide uniform and expedited care for adult trauma patients taking preinjury anticoagulants and antiplatelet medications with suspected head injury. The purpose of this article is to describe the development and implementation of the head strike protocol and compare time metrics and outcomes before and after implementing the protocol. Per the head strike protocol, patients with suspected traumatic intracranial hemorrhage (tICH) were screened for anticoagulants or antiplatelet medications by emergency medical service personnel/at first contact, activated as a Level II trauma and received a computed tomographic scan of the head within 30 min of arrival, and started reversal of blood products within 30 min of tICH confirmation. Compared with patients admitted before establishing the head strike protocol, patients treated postimplementation were significantly more likely to have trauma team activation (77% preprotocol vs. 89% postprotocol) and expeditious initiation of reversal agents (68 min preprotocol vs. 21 min postprotocol) and to survive their head injury for patients taking anticoagulants (42% preprotocol vs. 21% postprotocol). There were no differences in mortality for patients taking antiplatelet agents. This comprehensive nurse-driven reversal protocol presents an algorithm for managing patients with suspected tICH taking any preinjury blood thinners, allowing "ownership" by the nursing staff to ensure there are no delays in initiating blood products. This protocol may be particularly salient with the aging of the trauma population and parallel increase in the use of blood thinners.